2007
DOI: 10.1097/sla.0b013e31814699a2
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Paradigms in the Treatment of Lower Extremity Vascular Disease

Abstract: Percutaneous therapy for peripheral vascular disease is associated with minimal mortality and can achieve 2-year secondary patency rates of nearly 80% in patients with claudication. Although patency is diminished in patients with limb-threat, limb-salvage rates remain reasonable at close to 80% at 2 years. Percutaneous infra-inguinal revascularization carries a low risk of morbidity and mortality, and should be considered first-line therapy in patients with chronic lower extremity ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(60 citation statements)
references
References 44 publications
1
57
0
2
Order By: Relevance
“…7,13 Recent studies have shown that BA access can be a safe and effective alternative to femoral access, with complication rates of between 1.3% and 3.4% reported. 2,3,10,14 The complication rate in our patients requiring intervention or admission was 1.9%. Our low complication rate can be attributed to the routine use of ultrasound guidance, 4F micropuncture kits, and dedicated hold team nurses who are specially trained to hold BA access sites.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…7,13 Recent studies have shown that BA access can be a safe and effective alternative to femoral access, with complication rates of between 1.3% and 3.4% reported. 2,3,10,14 The complication rate in our patients requiring intervention or admission was 1.9%. Our low complication rate can be attributed to the routine use of ultrasound guidance, 4F micropuncture kits, and dedicated hold team nurses who are specially trained to hold BA access sites.…”
Section: Discussionmentioning
confidence: 93%
“…[2][3][4][5]13 Failure of access can be attributed to multiple prior procedures on the artery, arterial spasm, and arterial dissection. 7 BA access offers a full range of interventions to all clinically relevant arterial regions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 A number of studies have reported hypercholesterolemia as an independent predictor of poor outcome after a patient undergoes revascularization for PAD. [9][10][11] Apolipoprotein E (ApoE) is a glycoprotein synthesized by the liver and macrophages and is a constituent of plasma lipoproteins. 12,13 It serves as a ligand for the cell-surface lipoprotein receptors and therefore is important in clearing lipoprotein remnants from the circulation.…”
mentioning
confidence: 99%
“…Previous studies have suggested favorable EVT outcomes for CLI, [13][14][15][16] but at the same time they have revealed contradictory results about the relative benefit of EVT in comparison with bypass surgery. Although the Bypass versus Angioplasty in Severe Ischemia of the Leg trial showed better long-term amputation-free survival outcomes after bypass surgery on autologous veins compared with EVT, 17 a major amputation has been reported to be necessary in ≈10% of patients with ischemic ulcers of the lower limbs despite a patent bypass.…”
Section: Discussionmentioning
confidence: 98%